Impact of carbonation on reinforced concrete structures, considering the increase of CO2 due to climate change in Brazil - Chiara Pinheiro Teodoro; Rogério Carrazedo (Revista IBRACON de Estruturas e Materiais)
Abstract Corrosion in reinforced concrete structures has become a growing concern, primarily due to climate change-related factors such as the rise of carbon dioxide levels, temperature fluctuations, and altered precipitation patterns. To address this, regional assessments are vital due to varying environmental impacts. This study examines corrosion in Brazil, focusing on urban CO2 levels, employing NBR 6118 (2023) to predict depassivation, initial cracks, and failure due to excessive displacement (Serviceability Limit State). Results indicate a 50% depassivation probability within 13 years for a 2.5 cm concrete cover in the worst-case scenario. Additionally, the diameter of reinforcements greatly influences failure probability for excessive displacement, with a 311% increase over 45 years using a 5 mm diameter instead of 10 mm. These findings underscore the urgency of adapting construction practices to consider accelerated carbonation rates in urban environments and the need for ongoing research to refine predictive models and update construction standards accordingly.